ANALISIS NILAI MORAL PADA FILM" BILA ESOK IBU TIADA" KARYA NUY NANIGA” - Pasaribu, Gumarpi Rahis; Febriyanti, Ayu; Khoirunisa, Khoirunisa; Muliatik, Sri (LUMBUNG AKSARA, 2025)
This research aims to analyze the moral values contained in the film Bila Esok Ibu Tiada. This film raises the theme of family conflict, responsibility, and the value of sacrifice in caring for parents. The research method used is qualitative descriptive with data collection techniques through direct observation of films and analysis of dialogues and scenes. The results of the study show that this film contains various moral values, such as children's responsibilities to parents, the importance of communication in the family, gender equality, and the consequences of neglect of parents. The director conveys a moral message through storylines, characterizations, and the use of cinematic elements such as lighting, shooting, and background music. Analysis based on Bertens' moral theory shows that moral values in this film are related to responsibility, conscience, absolute obligation, and formal nature.